Degradation of the Textile Dye Reactive Black 5 by Basidiomycetes - Leonardo Pellizzari Wielewski; Tatiana Zuccolotto; Marlene Soares; Liziê Daniela Tentler Prola; Marcus Vinicius de Liz (Revista Ambiente & Água, 2020)
Reactive Black 5 (RB5) is one of the synthetic reactive dyes most used in the textile industry, due to its solubility in water and reactive groups which form covalent bonds within the fiber. In the process of dyeing fabrics, however, it is estimated that 12-14% of dyes are released into the effluent. This work evaluated the biodegradation of RB5 dye, adsorbed in polyurethane foam, by basidiomycetes (Phanerochaete chrysosporium ATCC 24725, Pleurotus ostreatus and Pleurotus floridae). Results were evaluated considering the partial- or total medium discoloration, the adsorption capacity of the dye in the polyurethane foam (PUF) and the respirometric measurements. The results showed that Phanerochaete chrysosporium was able to partially degrade 50 mg L-1 of RB5 in pH 6.0, when cultivated in Petri dishes. When this microorganism was cultivated in PUF cubes saturated with RB5 solution (50 mg L-1, pH 6.0), CO2 production reached an accumulated value of 2.16 mg on the fifteenth day, revealing the growth of the microorganism and consequently the contaminant degradation, which was used as the source of nutrients.